Financial security of military judges in South Africa - Tshivhase, Aifheli Enos (Scientia Militaria - South African Journal of Military Studies, 2017)
The status of military courts within the South African judicial system is uncertain. This uncertainty makes it challenging to determine the acceptable degree of their independence, including determining the acceptable basic financial security of military judges. In Van Rooyen v The State (2002) 5 SA 246 (CC), the Constitutional Court accepted a lower standard of independence in relation to magistrate’s courts than it requires of the High Courts. It did this primarily because the Constitution provides for a hierarchy of courts and, in its view, this justifies the different degrees of independence of the various courts. This article will report on a systematic investigation into the status of military courts within the South African court hierarchy mainly in comparison with magistrate’s courts with the aim of making a recommendation on the appropriate level of remuneration for military judges.